PEDAGOGICAL SKILLS IN TEACHING HISTORY IN GENERAL SECONDARY SCHOOLS - Khusainbekova Gulchira (Western European Studies, 2024)
Pedagogical skill and its components in the methodology of history are highlighted in this article
Keywords: History; pedagogue; pedagogical skill; ability